The HIF-1α/CXCR4 pathway supports hypoxia-induced metastasis of human osteosarcoma cells. Issue 1 (1st February 2015) - Guan, Guofeng; Zhang, Yinglong; Lu, Yao; Liu, Lijuan; Shi, Doufei; Wen, Yanhua; Yang, Lianjia; Ma, Qiong; Liu, Tao; Zhu, Xiaodong; Qiu, Xiuchun; Zhou, Yong
Abstract HIF-1α mediates hypoxia-induced expression of the chemokine receptor CXCR4 and contributes to metastasis in many different cancers. We have previously shown that hypoxia promotes migration of human osteosarcoma cells by activating the HIF-1α/CXCR4 pathway. Here, immunohistochemical analysis showed that unlike control osteochondroma samples, osteosarcoma specimens were characterized by elevated expression levels of HIF-1α and CXCR4. Moreover, we found that hypoxia-induced invasiveness was more pronounced in high metastatic potential F5M2 osteosarcoma cells than in low metastatic potential F4 cells, and that this induction was sensitive to treatment with the CXCR4 antagonist AMD3100 and the HIF-1α inhibitor KC7F2. Interestingly, hypoxia-induced CXCR4 expression persisted after cultured osteosarcoma cells were returned to normoxic conditions. These observations were confirmed by experiments in a mouse model of osteosarcoma lung metastasis showing that hypoxia stimulation of pulmonary metastasis was greater in F5M2 than in F4 cells, and was sensitive to treatment with AMD3100. Our study provides further evidence of the contributions of hypoxia and the HIF-1α/CXCR4 pathway to the progression of osteosarcoma, and suggests that this axis might be efficiently leveraged in the development of novel osteosarcoma therapeutics.